A survey to evaluate facilitators and barriers to quality measurement and improvement: Adapting tools for implementation research in palliative care programs - Dy, Sydney M. (J Pain Symptom Manage, 2017)
CONTEXT: Though critical for improving patient outcomes, palliative care quality indicators are not yet widely used. Better understanding of facilitators and barriers to palliative care quality measurement and improvement might improve their use and program quality. OBJECTIVES: Development of a survey tool to assess palliative care team perspectives on facilitators and barriers to quality measurement and improvement in palliative care programs. METHODS: We used the adapted Consolidated Framework for Implementation Research to define domains and constructs to select instruments. We assembled a draft survey and assessed content validity through pilot testing and cognitive interviews with experts and front-line practitioners for key items. We analyzed responses using a constant comparative process to assess survey item issues and potential solutions. We developed a final survey using these results. RESULTS: The survey includes five published instruments and two additional item sets. Domains include organizational characteristics, individual and team characteristics, intervention characteristics and process of implementation. Survey modules include Quality Improvement in Palliative Care, Implementing Quality Improvement in the Palliative Care Program, Teamwork and Communication, Measuring the Quality of Palliative Care, and Palliative Care Quality in Your Program. Key refinements from cognitive interviews included item wording on palliative care team members, programs and quality issues. CONCLUSION: This novel, adaptable instrument assesses palliative care team perspectives on barriers and facilitators for quality measurement and improvement in palliative care programs. Next steps include evaluation of the survey’s construct validity and how survey results correlate with findings from program quality initiatives.